2014
DOI: 10.1016/j.apergo.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of mental models in home heat control: Searching for feedback, valve, timer and switch theories

Abstract: An intergroup case study was undertaken to determine if: 1) There exist distinct mental models of home heating function, that differ significantly from the actual functioning of UK heating systems; and 2) Mental models of thermostat function can be categorized according to Kempton's (1986) valve and feedback shared theories, and others from the literature. Distinct, inaccurate mental models of the heating system, as well as thermostat devices in isolation, were described. It was possible to categorise thermost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
2
37
1
Order By: Relevance
“…For example, people with higher numeracy skills tend to be more accurate in their judgements of energy consumption (Attari et al, 2010;Schley & DeKay, 2015). Kempton (1986) and Revell and Stanton (2014) also found variation between people in their mental models of central heating systems.…”
Section: Individual Differences In Perceptions Of Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, people with higher numeracy skills tend to be more accurate in their judgements of energy consumption (Attari et al, 2010;Schley & DeKay, 2015). Kempton (1986) and Revell and Stanton (2014) also found variation between people in their mental models of central heating systems.…”
Section: Individual Differences In Perceptions Of Energy Consumptionmentioning
confidence: 99%
“…More recently, Revell and Stanton (2014) showed that householders might hold various mental models of central heating systems that vary greatly from how the systems actually work. As Norman (1983) pointed out, it is not necessary for people to have accurate mental models of a device or system in order to use it but they must have models that produce the result they want.…”
Section: Introductionmentioning
confidence: 99%
“…The second branch stepped out of psychology and applied mental models to support better interaction between people and the external world. Typical research interests include the role of mental models in learning and training [12][13][14][15] and using computers and appliances [16][17][18][19].…”
Section: Mental Modelsmentioning
confidence: 99%
“…Mental models can make an important contribution to improving building literacy [5,6] because they describe people's beliefs about a system, its elements and connections, which guide actions. As people strive to achieve warmth and comfort in their homes, everyday actions contribute to energy use (and efficiency).…”
Section: 1: Energy Use and Occupantsmentioning
confidence: 99%
“…Instead of technical references, drawings expressed the idea of energy being 'magic', energy being everywhere, and drawn elements often related to natural imagery (sun, waves, wind and lightning) but also to infrastructure (pylons). In addition, Revell & Stanton's [6] study showed that people can hold distinct and incongruent models of their heating system. A group of six overseas postgraduates, living in the UK, had incomplete representations of the heating system and bypassed using the thermostat device altogether.…”
Section: Mental Models Of Heating Systemsmentioning
confidence: 99%